First-line immune-checkpoint inhibitor combination therapy for chemotherapy-eligible patients with metastatic urothelial carcinoma: A systematic review and meta-analysis - Mori, Keiichiro; Pradere, Benjamin; Moschini, Marco; Mostafaei, Hadi; Laukhtina, Ekaterina; Schuettfort, Victor M; Sari Motlagh, Reza; Soria, Francesco; Teoh, Jeremy Y C; Egawa, Shin; Powles, Thomas; Shariat, Shahrokh F; et al. (European journal of cancer (Oxford, England, 2021)
INTRODUCTION: Platinum-based combination chemotherapy is the standard treatment for patients with chemotherapy-eligible metastatic urothelial carcinoma (mUC). Immune-checkpoint inhibitors (ICIs) are currently assessed in this setting. This review aimed to assess the role of ICIs alone or in combination as first-line treatment in chemotherapy-eligible patients with mUC. METHODS: Multiple databases were searched for articles published until November 2020. Studies were deemed eligible if they compared overall survival (OS), progression-free survival (PFS), objective response rates (ORRs), complete response rates (CRRs), durations of response (DORs) and adverse events (AEs) in chemotherapy-eligible patients with mUC. RESULTS: Three studies met our eligibility criteria. ICI combination therapy was associated with significantly better OS and PFS, higher CRR and longer DOR than chemotherapy alone (hazard ratio [HR]: 0.85, 95% confidence interval [CI]: 0.76-0.94, P = 0.002; HR: 0.80, 95% CI: 0.71-0.90, P = 0.0002; odds ratio [OR]: 1.48, 95% CI: 1.12-1.96, P = 0.006; and mean difference: 1.39, 95% CI: 0.31-2.46, P = 0.01, respectively). ICI-chemotherapy combination therapy was also associated with significantly better OS and PFS, higher ORR and CRR and longer DOR than chemotherapy alone. Although OS and PFS benefits of ICI combination therapy were larger in patients with high expression of programmed death-ligand 1 (PD-L1), PD-L1 low expression patients also had a benefit; HR for OS (high PD-L1: HR 0.79 versus low PD-L1: HR 0.89) and PFS (high PD-L1: HR 0.74 versus low PD-L1: HR 0.82). ICI monotherapy was not associated with better oncological outcomes but was associated with better safety outcomes than chemotherapy alone. CONCLUSIONS: Our analysis indicates a superior oncologic benefit to first-line ICI combination therapies in patients with chemotherapy-eligible mUC over standard chemotherapy. In contrast, ICI monotherapy was associated with favorable safety outcomes compared with chemotherapy but failed to show its superiority over chemotherapy in oncological benefits. PD-L1 status alone cannot help guide treatment decision-making. However, caution should be exercised in interpreting the conclusions drawn from this study, given that there is the heterogeneity of the population of interest, risk of bias and the nature of the studies evaluated whose data remain immature or unpublished.
Keywords: Male; Immune Checkpoint Inhibitors; výběr pacientů; doba přežití bez progrese choroby; Antineoplastic Combined Chemotherapy Protocols; B7-H1 Antigen; nádory močového měchýře; Clinical Decision-Making; urotel; Immune-checkpoint inhibitor; Adult; Aged; dospělí; mužské pohlaví; senioři; Patient Selection; Urothelium; Time Factors; Urothelial carcinoma; senioři nad 80 let; lidé; Carcinoma; ženské pohlaví; Humans; protokoly protinádorové kombinované chemoterapie; Meta-analysis; časové faktory; karcinom; Aged, 80 and over; antigeny CD274; Programmed death-ligand 1; inhibitory kontrolních bodů; Urinary Bladder Neoplasms; klinické rozhodování; Female; Progression-Free Survival; lidé středního věku; Middle Aged